Karakteristik Sensori dan Kandungan Protein Putu Ayu Berbahan Air Kelapa dan Tepung Kulit Buah Naga Merah - Ira Handayani; Siva Ma’rifatul Fadhilah; Ndaru Prasastono (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The purpose of this research are 1) knowing the acceptability of putu ayu with coconut water and red dragon fruit peel flour which is most preferred by the panelists, 2) knowing the best recipe formula 3) knowing the protein content of putu ayu with coconut water and dragon fruit peel flour as ingredients. red is the panelists' favorite. This research method uses literature, documents, experiments, sensory evaluation and chemical tests. The results showed that putu ayu with coconut water and red dragon fruit peel flour Formula A was most liked and accepted by the panelists. The best putu ayu recipe formula uses coconut water and red dragon fruit skin flour. Formula A is 237.5 g wheat flour, 12.5 g red dragon fruit skin flour, 200 ml old coconut water, 3 eggs, 200 g granulated sugar, 1 tsp SP, and 1 grated coconut. Based on the results of chemical tests for the protein content of putu ayu using coconut water and red dragon fruit peel flour, formula A per 100 g is 6.117% protein.